2019
DOI: 10.1186/s13568-019-0872-8
|View full text |Cite
|
Sign up to set email alerts
|

Algicidal bacterium CZBC1 inhibits the growth of Oscillatoria chlorina, Oscillatoria tenuis, and Oscillatoria planctonica

Abstract: Frequent harmful cyanobacteria blooms limit the sustainable development of aquaculture. Algicidal bacteria can efficiently control harmful algae without secondary pollution. The algicidal bacteria CZBC1 can lyse Oscillatoria spp. and other harmful cyanobacteria, but its effector mechanism and algicidal threshold are unknown. In this study, we examined the algicidal effect of CZBC1 on O. chlorina, O. tenuis, and O. planctonica by microscopic enumeration and scanning electron microscopy observation. Then, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…For C. raciborskii, this is the rst study investigating the algicidal and lytic activity of a bacterial strain against this toxic cyanobacterium. Generally, the mechanisms underlying the inhibitory and lysing activity of algicidal bacteria can be through direct physical contact between bacterial and cyanobacterial cells, or indirectly via excretion of extracellular chemicals or enzymes by bacteria into the surrounding medium (Luo et al 2013;Lee et al 2018, Hu et al 2019. In this study, the ltrate of bacterial strain SSZ01 inhibited the growth of C. racibrskii during the rst day of incubation, while the inhibition and lysis of C. raciborskii cells co-cultivated with SSZ01 cells commenced after 3 days of incubation.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…For C. raciborskii, this is the rst study investigating the algicidal and lytic activity of a bacterial strain against this toxic cyanobacterium. Generally, the mechanisms underlying the inhibitory and lysing activity of algicidal bacteria can be through direct physical contact between bacterial and cyanobacterial cells, or indirectly via excretion of extracellular chemicals or enzymes by bacteria into the surrounding medium (Luo et al 2013;Lee et al 2018, Hu et al 2019. In this study, the ltrate of bacterial strain SSZ01 inhibited the growth of C. racibrskii during the rst day of incubation, while the inhibition and lysis of C. raciborskii cells co-cultivated with SSZ01 cells commenced after 3 days of incubation.…”
Section: Discussionmentioning
confidence: 69%
“…The results showed that the co-cultivation of C. raciborskii with bacterial cells resulted in the reduction of C. raciborskii cell density, with complete cell lysis within 5 days. The removal e ciency of C. raciborskii cells by our bacterial strain can be compared to that of the strongest algicidal bacteria reported in previous studies, such as Aeromonas and Bacillus, which completely removed and lysed cyanobacterial cells of M. aeruginosa and Oscillatroia planctonica from 5 to 6 days (Lee et al 2018, Hu et al 2019Yang et al 2020). For C. raciborskii, this is the rst study investigating the algicidal and lytic activity of a bacterial strain against this toxic cyanobacterium.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…against M. aeruginosa also re ected this trend of algicidal mechanism (Yang et al 2020). Similarly, Oscillatoria planctonica cells were lysed by extracellular products of Bacillus cereus CZBC1 (Hu et al 2019). Most of these studies demonstrated that the lytic activity of algicidal bacteria are associating with initial cell density of bacteria (Hu et al 2019;Yang et al 2020).…”
Section: Discussionmentioning
confidence: 99%